WOBBLE RIBBED DESIGN-ORTHOTROPIC CYLINDRICAL SHELLS WITH FILLER, UNDER AXIAL COMPRESSION AND GIVEN FRICTION - Latifov, F. S.; Agalarova, I. U. (Computer Science and Applied Mathematics, 2016)
This article is devoted to the study of free oscillations of structurally-orthotropic cylindrical shells with a solid filler, ysilennymi cross ribs under axial compression systems and taking into account the friction between the contact surfaces of the shell and the core. aggregate movement described by systems of equations of the theory of elasticity in displacements. With the help of the contact conditions for finding the frequency of free oscillations of structurally-orthotropic cylindrical shells with filler, ysilennymi cross ribs under axial compression systems and taking into account the friction between the contact surfaces of the shell and filler frequency equation is built and implemented numerically. Influence of the inertial properties of the filler in the process of system oscillations investigated in two cases: a) the effects of the inertial properties of the process of system oscillations can be neglected; b) the effect of the inertial properties of the system to process fluctuations significantly.